OPERATION DYNAMICS OF ADAPTIVE FRICTIONAL CLUTCH WITH DIFFERENTIATED FRICTION COUPLES - Alexander E. Fokin; Maxim D. Gavrilenko; Mikhail P. Shishkarev (Advanced Engineering Research, 2011)
The problem on the stipulation conditions for the stationary mode of the drive self-oscillation regime on the basis of the operation analysis of the multiplate adaptive frictional clutch of N. D. Verner’s construction is solved. Its frictional group consists of the disks made from the materials with various friction factor magnitudes.